2010
DOI: 10.1200/jco.2009.24.6298
|View full text |Cite
|
Sign up to set email alerts
|

Positron Emission Tomography With [18F]Fluorodeoxyglucose Improves Staging and Patient Management in Patients With Head and Neck Squamous Cell Carcinoma: A Multicenter Prospective Study

Abstract: PURPOSE To address the impact of positron emission tomography with [(18)F]fluorodeoxyglucose (PET-FDG) on the initial staging and management of patients with head and neck squamous cell carcinoma (HNSCC). PATIENTS AND METHODS This multicenter, prospective study included 233 patients with newly diagnosed and untreated HNSCC. TNM stage and therapeutic decision were first determined based on the conventional work-up (including physical examination, computed tomography [CT]/magnetic resonance imaging of the head a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
121
2
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 210 publications
(134 citation statements)
references
References 26 publications
8
121
2
3
Order By: Relevance
“…PET-CT findings in this study are in agreement with this data confirming that PET-CT could accurately detect nodal disease in the staging of head and neck cancer patients. Furthermore, several studies have already shown that adding PET-FDG or PET/CT-FDG to standard work-up led to a higher staging accuracy with higher specificity [18][19][20][21].…”
Section: Discussionmentioning
confidence: 99%
“…PET-CT findings in this study are in agreement with this data confirming that PET-CT could accurately detect nodal disease in the staging of head and neck cancer patients. Furthermore, several studies have already shown that adding PET-FDG or PET/CT-FDG to standard work-up led to a higher staging accuracy with higher specificity [18][19][20][21].…”
Section: Discussionmentioning
confidence: 99%
“…Lonneux et al (10) have developed a prospective study aimed at evaluating the use of PET/CT in the initial staging of head and neck cancer and its impact on the therapeutic decision making. The authors have found disagreement in relation to initial staging in 43% of the cases.…”
Section: Discussionmentioning
confidence: 99%
“…In head and neck oncology, the main clinical situations comprise the initial staging and investigation of lymph node metastatic disease (7,8) and hematogenic disease, detection of primary lesions in cases of occult primary tumors (9) , evaluation of response to radiotherapy and/or chemotherapy, and investigation of early recurrence of disease and second primary tumor. In all such conditions changes in the approach may potentially occur (10) . In some series, the second tumor incidence ranged between 11.1% and 12.9% (11,12) , while lymph node disease presented specificity of 87% to 100% and sensitivity between 47% and 100% (13) .…”
Section: Introductionmentioning
confidence: 99%
“…For primary tumor diagnosis, 18 F FDG-PET imaging showed a significant better sensitivity (93% vs 65%) and specificity (70% vs 56%) over CT (Gambhir et al, 2001). PET imaging allows a more accurate nodal staging of locally advanced head and neck cancer (Kyzas et al, 2008;Yoo et al, 2013), and could result in changing the therapeutic management in nearly 15% of patients (Lonneux et al, 2010). For patients with cervical node metastases of unknown primary, PET/CT detected a primary tumor in nearly 30% of patients (Rudmik et al, 2011;Wong et al, 2012;Zhu and Wang, 2013).…”
Section: Introductionmentioning
confidence: 99%